Zoonotic disease concerns in animal-assisted therapy and animal visitation programs - Waltner-Toews, David (1993)
A survey was done of 150 systematically selected United States animal care agencies and 74 Canadian humane societies to determine the prevalence of animal assisted therapy (AAT) programs; concerns about, and experience with, zoonotic diseases; and precautions taken to prevent zoonotic disease transmission. Of the 69 US agencies and 49 Canadian societies that reported having AAT programs, 94% used dogs and/or cats in their programs, 28% used rabbits, 15% used “pocket pets” (hamsters, gerbils, mice, guinea pigs), and 10% used birds (excluding poultry). About two-thirds of the programs were involved with the elderly in nursing homes, about a quarter of them worked with schools, and a quarter worked with hospitals. Half of the respondents had concerns about zoonotic disease control. Rabies, ringworm, and external parasitism were the most commonly cited zoonotic diseases of concern. Few concerns were based on actual experience. Fewer than half of the programs consulted a health professional about prevention of zoonotic diseases. Only 10% of the respondents reported having printed guidelines about the prevention of zoonotic disease transmission. Practising veterinarians are encouraged to make their expertise available to local AAT programs.